Research on Internal Current Sharing of High-power IGBTs - YU Wei; LUO Haihui; DENG Jianghui; ZHOU Wangjun; JIANG Pusheng; WU Yudong (Kongzhi Yu Xinxi Jishu)
In order to increase the rating current level of device, high power IGBT is often composed of multiple chips and subelements in parallel, and in this case, how to effectively control the current sharing within device is very important. It analysed the important influence of stray inductance on IGBTs internal current sharing by experimental research, deduced and analyzed theoretically the influence of chip parameters on static current sharing, and verified the influence of chip parameters on dynamic current sharing by experiment and simulation. The results showed that the influence of the asymmetry of the parasitic parameters on current sharing is greater than that of chip parameters, and the influence of both on turning-on current sharing is greater than that of the turning-off.